Norms beyond Empire Law-Making and Local Normativities in Iberian Asia, 1500-1800 - Bastias Saavedra, Manuel (Max Planck Studies in Global Legal History of the Iberian Worlds, 2021)
Norms beyond Empire seeks to rethink the relationship between law and empire by emphasizing local normative production. Its ten chapters explore normative production by focusing on case studies from the Iberian empires in China, India, Japan, and the Philippines. ; Readership: All interested in legal history, the history of Christianity in Asia, the history of Spanish and Portuguese imperialism, early modern colonialism, missionary history, global history, and legal pluralism.